Robustness of exponential dichotomies of boundary-value problems for general first-order hyperbolic systems - Kmit, I. Ya.; Recke, L.; Tkachenko, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We examine the robustness of exponential dichotomies of boundary-value problems for general linear first-order one-dimensional hyperbolic systems. It is assumed that the boundary conditions guarantee an increase in the smoothness of solutions in a finite time interval, which includes reflection boundary conditions. We show that the dichotomy survives in the space of continuous functions under small perturbations of all coefficients in the differential equations.